Peranan Media Digital Dalam Mempertahankan Budaya Lokal Indonesia Di Era Globalisasi - Johan Arifin (Jurnal Ilmiah Kanderang Tingang, 2023)
There is no globalization without advancement of information and communication technology. The spread of information take place quickly and expand, not restricted to developed countries with the high economic growth, but also across the borders of the poor and developing countries with low economic growth. For Indonesia, the inclusion of western values are riding the wave of globalization to the people of Indonesia are a threat to native culture that portray the typical locality of regions in this country. For example, small children can just look at pornographic images, teenagers are supposed to be a milestone in the nation's culture extolling hedonism and modernity. Hence, be required the strategies that in fact take advantage of the role of digital media in prevent the negative effects from the outside because of the globalization, among others websites, mobile applications, mobile games, and so on can be used to a basis of the approach to spreading out the culture of Indonesia through the Internet with the emphasis of spread through blogs and social media, make a local media into a national and international media were able to increase the role of local culture on the world stage and last, execute a counter culture, which is a kind of effort from a local media to impede the effects from outside media by the accentuate of the characteristic that originate the local community.